Insecticidal activity of aqueous extracts of some medicinal plants on stages of south beetle beans Callosobruchus maculatus (Fab.) - Adnan Mohammed; Doaa Abdul-Rahman (College of Education for Pure Sciences, 2019)
The current study examines the effect of six concentrations of aqueous extracts which are 2.5, 5, 10, 15, 20 and 25% of four medicinal plants on the biological aspects of south beetle beans Callosobruchus maculatus. These plants belong to the family Umbellifera, they are: Coriandor Coriandrum sativum, Cumin Cuminum cyminum, Fennel Foericulum vulgare and Anise Pimpinella anisum. The activity test of these plants was done by soaking chickpeas seeds (the food of the insect) in the previous extracts. The aqueous extracts of Coriandor, Fennel and Anise cause 100% killing of the larval and pupal stages at 25% concentration. The treatment had a significant effect on some of the biological aspects of the first generation pregnancy, since the female productivity decreased to 20.53% at the concentration 25%. Also egg retention occurred in anise treatment. While the productivity of control treatment was 79.26%, also eggs retention was occurred in the female of the southern cowpea beetle which reached 41.70% in Anise treatment at the concentration 2.5%. The study proved that the almost of the above treatments affected the eggs viability of the first generation females.